Europe Within the World of Regionalisms - BACH, Daniel C. (Przegląd Strategiczny, 2018)
The surge of diversified forms of regionalism and regional integration within the past few decades has stimulated the reappraisal of the conceptual tools traditionally designed to bench-mark and monitor region-building processes across the world. More recently, the Brexit negotiations have become a reminder that the EU remains an unfolding experience. This article argues that the study of African regionalisms constitutes a timely invitation to revisit the experience of the EU and its contribution to the world of regionalisms. After a brief survey of the classic definition of the region, we will discuss the ongoing relevance of European integration and the implications of the analytical distinction between regionalism, regionalisation and regional integration, before drawing from the study of Africa five threads which set the basis for a comparative study of regions and regionalisms beyond the classic emphasis on the EU or the world of regions.